Discussion Paper on More Adequate and Effective IT Tools. Some Previous Results Concerning More Adequate and Effective ICT Tools in the Category: Tools for Making Presentations - Smyrnova-Trybulska, E.; Ogrodzka-Mazur, E.; Szafranska-Gajdizca, A.; Morze, N.; Makhachashvili, R.; Drlik, M.; Capay, M.; Tomanova, J.; Svec, P.; Issa, Tomayess; Issa, Theodora; Romanyukha, M.; et al. (2015)
The article describes some preliminary results of the implementation of Work-Package 4 (WP4) “Selection and testing new IT tools” in the framework of the international research network (IRNet) and researchers from partner institutions from Poland, Slovakia, Ukraine, and Australia. These results concern analysis and study of some categories of IT tools for making multimedia presentation. All the package period has been divided into 5 main stages. The role of multimedia in teaching is considerable as it offers various formats of presenting information simultaneously. The combination of text, audio, images, animation, video, as well as hyperlinks has an advantage of using both of the two main channels – visual and verbal – for presentation in an efficient way. This paper also discusses the features of effective presentation and examples of computer programs which may be used for this purpose. Authors presented a ranking list based on quality and quantity assessment of chosen IT tools and they proposed some characteristics of good presentation as well as they analyzed frequent mistakes made by users elaborating presentations.